PENGARUH AKREDITASI TERHADAP KEBIJAKAN PENDIDIKAN DI SMP NEGERI 2 PUJUT: ANALISIS IMPLIKASI AKREDITASI B BERBASIS RAPOR PENDIDIKAN 2025 - LL. Herry Anggara, Erick; Roihatul Ilmi; Muhammad Sanusi; Marisa Arni; Basilius Redan Werang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT School accreditation is an external quality assurance mechanism expected to shape school policies, programs, and resource allocation. This study examines the implications of a B accreditation status for education policy at SMP Negeri 2 Pujut through a descriptive-evaluative case study. Data were obtained from the school profile, teacher records, the 2025 Education Report, data-based planning recommendations, and the Annual Work Plan and ARKAS worksheets. The analysis involved data reduction, indicator classification, comparison of 2024 and 2025 achievements, and document triangulation. The results show that accreditation is associated with stronger attention to learning outcomes and service standards. Literacy increased by 33.34 points to 66.67 percent, while numeracy increased by 28.88 points to 64.44 percent. However, implementation remained inconsistent. The school program and policy indicator declined by 4.10 points to 61.90. Anti-bullying policy decreased by 12.47 points, sexual violence prevention policy by 9.01 points, and spending on teacher quality improvement reached only 2.76 percent. The facility index was 70.90, but room feasibility was only 22.22. The Annual Work Plan and ARKAS did not yet contain operational programs. Accreditation has therefore triggered a quality agenda, but it has not fully functioned as a continuous policy control system. The school should integrate accreditation findings and Education Report data into annual planning, budgeting, performance indicators, and quarterly evaluation.